The Influence of Students’ Initial Knowledge and Students’ Learning Motivation on the Learning Outcomes - Limbong, Ike Pratiwi Br; Nasution, Toni (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2025)
This research aims to analyze the influence of prior knowledge and learning motivation on the learning outcomes of class VII students at SMP IT Al Ikhwan Tanjung Morawa. Carried out in May-June 2024 with a population of 126 students, the research used a total sampling method. Data analysis includes validity, reliability, normality, correlation, regression and hypothesis tests. The research results showed that all measurement instruments for initial knowledge and learning motivation were declared valid and reliable. The normality test shows that the data is normally distributed. The correlation test revealed a significant relationship between prior knowledge (r = 0.601) and learning motivation (r = 0.486) on learning outcomes. Multiple linear regression analysis produces the equation Y = 32.638 + 0.393X1 + 0.259X2, which shows that both prior knowledge and learning motivation have a significant positive influence on student learning outcomes. Hypothesis testing shows that the t-values ​​for prior knowledge and learning motivation are 6.017 and 3.172 respectively, with a significance of 0.000 and 0.002, both of which are smaller than 0.05. The F test shows that the simultaneous influence of the two independent variables on learning outcomes is also significant, with an F-calculated value of 42.662. These results emphasize the importance of prior knowledge and motivation in improving student learning outcomes.